2011
DOI: 10.1089/ars.2010.3353
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Neuropeptide Y Synthesis During Intermittent Hypoxia in the Rat Adrenal Medulla: Role of Reactive Oxygen Species–Dependent Alterations in Precursor Peptide Processing

Abstract: Intermittent hypoxia (IH) associated with recurrent apneas often leads to cardiovascular abnormalities. Previously, we showed that IH treatment elevates blood pressure and increases plasma catecholamines (CAs) in rats via reactive oxygen species (ROS)-dependent enhanced synthesis and secretion from the adrenal medulla (AM). Neuropeptide Y (NPY), a sympathetic neurotransmitter that colocalizes with CA in the AM, has been implicated in blood pressure regulation during persistent stress. Here, we investigated whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 77 publications
(108 reference statements)
2
12
0
Order By: Relevance
“…Given that CIH increases ROS levels in the carotid body (Peng et al 2003), these findings demonstrate that ROS‐dependent activation of ECE contributes to CIH‐induced ET‐1 upregulation in the rat carotid body. These observations are reminiscent of an earlier report showing that CIH‐induced upregulation of neuropeptide Y in the rat adrenal medulla is also mediated by ROS‐dependent activation of processing of neuropeptide Y from its precursor protein (Raghuraman et al 2011). The mechanism(s) by which ROS activates ECE, however, requires further investigation, which is beyond the scope of the present study.…”
Section: Discussionsupporting
confidence: 79%
“…Given that CIH increases ROS levels in the carotid body (Peng et al 2003), these findings demonstrate that ROS‐dependent activation of ECE contributes to CIH‐induced ET‐1 upregulation in the rat carotid body. These observations are reminiscent of an earlier report showing that CIH‐induced upregulation of neuropeptide Y in the rat adrenal medulla is also mediated by ROS‐dependent activation of processing of neuropeptide Y from its precursor protein (Raghuraman et al 2011). The mechanism(s) by which ROS activates ECE, however, requires further investigation, which is beyond the scope of the present study.…”
Section: Discussionsupporting
confidence: 79%
“…Real-time PCR was performed using a MiniOpticon system (Bio-Rad) with SYBR GreenER two-step quantitative RT-PCR kit (Invitrogen) as previously described (32). The primer sequences used for real-time PCR analysis of 18S, CYP11B2, Nox1, Nox2, Nox4, Nox5, and Duox1 in human and rat adrenal cortical cells are shown in Supplementary Table S1.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…Adrenal cortical slices were homogenized, and MDA levels in the homogenates were determined as a measure of lipid oxidation as previously described (32) and expressed as nanomoles per milligram of protein.…”
Section: Measurement Of Mdamentioning
confidence: 99%
“…It has been suggested that CH-evoked changes in NPY-like immunoreactivity in the carotid body and specific brain regions may contribute to adaptative mechanisms involving morphological changes in carotid bodies and alterations in sympathetic control and neuroendocrine function, respectively (92). IH (15 s paradigm) augmented NPY-like immunoreactivity in the rat brainstem (105) and markedly upregulated NPY expression in DBH-expressing adrenal chromaffin cells (96). IH-induced increase in NPY in the adrenal medulla was associated with ROS-dependent upregulation of prepro-NPY mRNA and protein as well as increased prepro-NPY processing.…”
Section: Effects Of Hypoxia On ␣-Amidated Peptide Synthesismentioning
confidence: 99%